2016
DOI: 10.17718/tojde.44090
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Motivation and Attitudes of Language Learners of Online Distance and Traditional in-Classroom Education

Abstract: In recent years, the increase in the use of computer and the internet has led to a change in the traditional concept of formal education today. Distance learning as a more studentcentered system has been frequently used at universities. In this context, education has been applied to the individuals consisting of all age groups in accordance with their aspirations, expectations and interest in a more flexible way. This study aims to determine and compare the motivation and attitudes of language learners of onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The constructivist-based instruction focuses on flexible and learner-defined goals, and, more importantly, better address personalized assessment [15]. When student's motivation and attitude is taken into consideration, the readiness for autonomy in language learning drives the motivation levels are higher than those of traditional in-class education [18]. It is understood since distance learners must regulate and oversee the rate and direction of their learning to a much greater degree than classroom learners.…”
Section: Answering Research Question and Discussionmentioning
confidence: 99%
“…The constructivist-based instruction focuses on flexible and learner-defined goals, and, more importantly, better address personalized assessment [15]. When student's motivation and attitude is taken into consideration, the readiness for autonomy in language learning drives the motivation levels are higher than those of traditional in-class education [18]. It is understood since distance learners must regulate and oversee the rate and direction of their learning to a much greater degree than classroom learners.…”
Section: Answering Research Question and Discussionmentioning
confidence: 99%
“…Similarly, Saadé et al (2007) identified that the success or failure of online learning is highly dependent on the intrinsic and extrinsic motivation of the learners. The dimension of "motivation for learning" will greatly facilitate the online learning, retention, and retrieval of information so that learners can fulfill their desires and efforts (Artino, 2008;Bekele, 2010;Buzdar et al, 2016;Chen et al, 2017;Firat, & Bozkurt, 2020;Genc et al, 2016;Horzum et al, 2015;Wei & Chou, 2020;Zhu et al, 2020).…”
Section: Motivation For Learningmentioning
confidence: 99%
“…Harandi and Safiyeh (2015) conducted research focusing on students" motivation in e-learning, the results show that e-learning was motivating them to work and they were engaged in learning ___________________________________________________________________________ successfully as they wanted to accomplish their aims and objectives in a more defined and motivated manner. Genc, Kulusakli, and Aydin, (2016) carried out a study in Turkey to reveal the motivational level of students for EFL e-learning, and further stated that the motivation of students is greatly affected by teachers" positive attitude and helping nature to set a particular goal and motivating environment for them. Motivation, CALL, and EFL Fandino et al (2019) asserted that there is a co-relation between CALL and motivation.…”
Section: ___________________________________________________________________________mentioning
confidence: 99%